2013
DOI: 10.1371/journal.pone.0061476
|View full text |Cite
|
Sign up to set email alerts
|

Consultant Input in Acute Medical Admissions and Patient Outcomes in Hospitals in England: A Multivariate Analysis

Abstract: Recent recommendations for physicians in the UK outline key aspects of care that should improve patient outcomes and experience in acute hospital care. Included in these recommendations are Consultant patterns of work to improve timeliness of clinical review and improve continuity of care. This study used a contemporaneous validated survey compared with clinical outcomes derived from Hospital Episode Statistics, between April 2009 and March 2010 from 91 acute hospital sites in England to evaluate systems of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(68 citation statements)
references
References 12 publications
3
62
3
Order By: Relevance
“…Increased consultant presence has been shown to be associated with reduced case-adjusted mortality rates in at least one publication. 19 From our work, two principles of workload distribution are clear:…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Increased consultant presence has been shown to be associated with reduced case-adjusted mortality rates in at least one publication. 19 From our work, two principles of workload distribution are clear:…”
Section: Discussionmentioning
confidence: 95%
“…Delays in patients being seen and workload increases have the potential to impact on mortality, morbidity and length of stay in hospital. 6,7 In order to ascertain objective criteria for staffing requirements, there is a need to better understand the workload of doctors and the timing of processes involved in routine aspects of medical care. The admission process is a key part of the acute medical team's role and the time requirements for this and related tasks will have implications on the staffing models and the overall efficiency of units.…”
Section: Introductionmentioning
confidence: 99%
“…Workload prevented doctors from fully discussing care with their patients and families, delayed discharges and affected the quality of handovers. 16 Both studies noted the negative impact of increased patient numbers and staffi ng shortages.…”
Section: Workload and Quality Of Carementioning
confidence: 99%
“…In the UK, Bell et al found that hospitals with more than 40 admissions per day had reduced case fatality rates (p≤0.03) but that patients on a high admission day had a longer mean length of stay (p≤0.02). 16 Conway et al analysed consultant admission numbers over a 10-year period in the UK. They found that patients admitted to consultants with the highest volume of admissions had shortened lengths of stay (p<0.001) and reduced 30-day in-hospital mortality (p<0.1) when compared to consultants with lower volume of admissions, suggesting that more practice does result in improved patient outcomes.…”
Section: Workload and Quality Of Carementioning
confidence: 99%
“…Getting senior opinions early is improving efficiencies in A&E and acute medical settings. 24,25 Consultant-led, strategic planning of MDT-delivered services driving aspirational standards in EEC provision is anticipated to be the future of EEC in the UK. …”
Section: The Future Of Eecmentioning
confidence: 99%